A GC-MS-Based Metabolomics Investigation of the Protective Effect of Liu-Wei-Di-Huang-Wan in Type 2 Diabetes Mellitus Mice. (13th August 2020) - Huang, Jian-hua; He, Dan; Chen, Lin; Du, Qing; Yu, Rong; Cai, Ping; Zhang, Shui-han
Abstract : Aim of the Study . The present study aimed to establish a metabolic profile and to investigate the changes of endogenous metabolites in diabetic mice treated with LWDHW. We further investigated the metabolic mechanism of action for the hypoglycemic activity of LWDHW and its possible role in reducing the risk of renal failure in type 2 diabetic mice. Materials and Methods . MKR mice were used for the development of diabetes with high-fat diet feeding. These mice were further injected with streptozocin (STZ) to aggravate kidney failure. Fasting blood glucose (FBG) and urinary albumin-to-creatinine ratio (ACR values) were determined to validate the successful establishment of diabetic models with desired kidney dysfunction. Metabolomics approach coupled with gas chromatography-mass spectrometry (GC-MS) and random forest (RF) algorithm was proposed to discover the metabolic differences among model group and control group as well as to examine the therapeutic efficacy of traditional Chinese medicine, Liu-Wei-Di-Huang-Wan (LWDHW), in diabetes and associated kidney failure. Results . Some metabolites such as 3-hydroxybutyric acid, citric acid, hexadecanoic acid, and octadecanoic acid showed significant differences between the control group and model group. Treatment with LWDHW resulted in a significant decrease in FBG and ACR values. These results suggested that LWDHW could have beneficial effects in diabetes-associated renal failure.